Who benefits? Australian public perceptions of safety and justice in connected and automated vehicles (CAVs) - Laura Martínez-Buelvas; Andry Rakotonirainy; Deanna Grant-Smith; Oscar Oviedo-Trespalacios (AI & SOCIETY, 2026)
Abstract The integration of connected and automated vehicles (CAVs) into everyday mobility systems raises profound ethical and societal challenges, particularly concerning safety, justice, and the treatment of vulnerable road users (VRUs). This study examines Australian public perceptions of the fairness, safety, and legitimacy of CAV deployment, investigating how exposure to information related to ethics and justice influences acceptance and evaluative perceptions related to trust (including perceived safety, fairness, and institutional confidence). An online survey of 384 respondents (aged 18–82) employed a before-and-after design, in which respondents evaluated CAVs before and after engaging with an infographic outlining key justice and safety dilemmas. Awareness of CAVs was widespread (95.3%), primarily shaped by media narratives rather than direct experience. Whilst over half of respondents expressed optimism about the potential of CAVs to improve safety and fairness, substantial proportions raised concerns about equity, transparency, and procedural justice. Following exposure to the infographic, positive perceptions declined slightly but not significantly, suggesting that attitudes are shaped by deeper moral and institutional expectations rather than informational effects. Open-ended responses revealed recurring anxieties about affordability, infrastructure readiness, technological reliability, and governance accountability, alongside ethical concerns related to VRU prioritisation, liability, privacy, and algorithmic decision-making in critical situations. These findings highlight a cautious public stance towards automation, one that accepts its promise but questions its fairness, underscoring the need for reflexive, transparent, and participatory governance frameworks to ensure that AI-driven mobility evolves in alignment with societal values and distributive justice.